PWE-015 HER2 expression in the Barrett's metaplasia-dysplasia-carcinoma sequence and potential targeting in vitro with the single chain antibody fragment C6.5. (28th May 2012) - Butt, M A; Haidry, R J; Oukrif, D; Pye, H; Stamati, I; Yahioglu, G; Rodriguez-Justo, M; Banks, M R; Deonarain, M P; Novelli, M R; Lovat, L B
Abstract : Introduction: There is increasing attention on the integration of targeted agents for oesophageal adenocarcinoma (OA) therapy. The most notable example of success of oesophagogastric targeted therapy was the addition of a HER2 targeting agent in the Phase III ToGA study. However, there is limited data on the expression of HER2 in the progression from Barrett's (BE) to OA. This study aimed to clarify expression in this sequence, and to show binding of C6.5, a single chain HER2 targeting human antibody Fv fragment (scFv), to known HER2 expressing OA cell lines in vitro. Efficacy of antibody based therapies can be enhanced by scFv's which penetrate tumours more quickly and demonstrate better tumour: normal tissue specificity. Methods: 33 paraffin embedded oesophageal tissue specimens were selected from patients with squamous (n=4), non-dysplastic BE (NDBE; n=4), low grade dysplasia (LGD; n=6), high grade dysplasia (HGD; n=8) and OA (n=12). Sections were immunostained with the automated Oracle Bond system (Leica, UK) for consistency. Staining was then scored by 2 expert pathologists according to the proportion of cells in the tissue staining positively as negative (<5%), borderline (5%–10%) or positive (>10%). In phase 2, binding of C6.5 scFv to the cancer cell lines SKOV-3 (ovarian), OE-19, OE-33 (oesophageal) and HT-29 (colon) was identified with flow cytometry using a mouse secondary followed by tertiary anti-mouse FITC. Data were then analysed with FlowJo software. Results: Significant expression of HER2 (>10% cells positive according to National Guidelines) was only seen in HGD (25%) and cancer (25%) specimens. Borderline staining (5%–10%) was seen in LGD (17%), HGD (13%) and cancer (8%). All NDBE and the remaining LGD, HGD and cancer samples were negative. Flow cytometry demonstrated C6.5 binding to SKOV-3, OE19 and OE-33 cells but not HT-29 cells. Conclusion: This study demonstrated that significant HER2 expression is only seen in roughly a quarter of patients with HGD and OA and not in NDBE or LGD. We also found that the HER2 targeting scFv C6.5 binds to breast cancer and OA cell lines but not colon cancer, the negative control. HER2 targeting therapies could therefore be postulated for patients with BE with HGD and OA, and these may be enhanced with scFv's such as C6.5. Competing interests: None declared.